Rancang Bangun Aplikasi Psikotalk Berbasis Android - Sari, Nova Noor Kamala; Jakkirahman , Jakkirahman; Sylviana, Felicia (Journal of Information Technology and Computer Science, 2022)
Advances in technology are currently happening in almost all aspects of life. Now all the desired information can be obtained using smartphone media. This is because the function of the smartphone can be used anywhere and anytime. One of the supporting factors is its relatively small size and easy to carry anywhere so that it makes it easy for users to find information. Advances and developments in this technology will certainly make it easier to present information, one of which is in the field of mental health. This study aims to design and build an android-based consulting application that connects psychologists with clients to conduct consultations in real time. This application presents a list of psychologists that can be selected according to the topic of consultation and clients can process payments and schedule consultations with psychologists through this application. This application can also provide information about the world of mental health through the information page provided. The results of this study are in the form of an android-based consulting application that can be used by psychology clients to conduct consultations with psychologists in real time through smartphone media.